Qualification testing of welders - fusion welding : - International Organization for Standardization
This document specifies the requirements for qualification of welders for fusion welding of aluminium and aluminium alloys. This document provides a set of technical rules for systematic qualification of welder which are independent of product type, location and examiner/examining body